Infused Oyster Mushroom (Pleurotus ostreatus) Inhibits Glucose Absorption through Intestinal Mucosal Membrane in Wistar Rats - Eko Fuji Ariyanto; Muhammad Nurhalim Shahib; Abdullah Firmansah Wargahadibrata (International Journal of Integrated Health Sciences, 2018)
Objective: To observe the effects of infused oyster mushroom (latin name: Pleurotus ostreatus) on glucose absorption through the intestinal mucosal membrane in Wistar rats.Methods: This study used experimental design. Subjects of this study were six Wistar rats which were randomly divided into two groups; three rats were used for the analysis of the most effective time for glucose absorption and the other three were used to evaluate the effect of infused oyster mushroom on glucose absorption. The intestine of subjects was connected to in situ perfusion machine. Control glucose solution (Ctr) or glucose solution containing 5% (Oys 5%), 10% (Oys 10%), and 20% (Oys 20%) infused oyster mushroom was added into the perfusion machine and flowed back and forth in the lumen of intestine subsequently, accompanied by washing procedures using 0.9% NaCl between treatments. The glucose concentration was determined using deproteinization method followed by absorbance measurement. Student’s t test was performed to analyze the difference between groups.Results: The level of glucose absorbed through intestinal mucosal membrane in control glucose solution and glucose solution with different concentrations of infused oyster mushroom, i.e. 5%, 10% or 20%, was 25.19+3.4 mg/dL, 16.27+0.86 mg/dL, 13.22+1.58 mg/dL and 10.03+1.25 mg/dL, respectively. Student’s t test showed significant differences between groups; Ctr and Oys 5% (p=0.03), Ctr and Oys 10% (p=0.02), and Ctr and Oys 20% (p=0.007).Conclusion: Infused oyster mushroom inhibits glucose absorption through intestinal mucosal membrane in Wistar rats.Keywords: Oyster mushroom (Pleurotus ostreatus), glucose absorption, intestine DOI: 10.15850/ijihs.v6n2.1354